“I Kept It to Myself”: Young Jamaican Men Who Have Sex with Men’s Experiences with Childhood Sexual Abuse and Sexual Assault - Harris, Orlando O.; Dunn, Leith Lorraine (Archives of sexual behavior, 2019)
The prevalence of HIV is exceptionally high among Jamaican men who have sex with men (JMSM) compared to similar populations within the Caribbean. A noticeable gap in the literature is the impact of childhood sexual abuse (CSA) and sexual assault on the state of the epidemic among this population. This study focused on JMSM’s experiences with CSA and sexual assault and how these domains relate to HIV prevention. We analyzed qualitative data from 20 semi-structured in-depth interviews and focus group discussions with 10 men. Common themes emerged that highlight the patterns and nature of the abuse, the characteristics of the perpetrators, and the ways in which participants engage agency and resiliency as a basis to reclaim personal power. These findings serve as a catalyst for understanding how experiences with CSA and sexual assault affect the lives of young JMSM; how those experiences may impact attitudes and behaviors regarding HIV testing, engagement in care; and have implications for shaping legal policy, clinical, and mental health services for JMSM survivors.